Safety and efficacy of stem cell therapy for treatment of neural damage in patients with multiple sclerosis - Jafarzadeh Bejargafshe, Mohammadmahdi (Stem Cell Investig, 2019)
Multiple sclerosis (MS) is a multifocal inflammatory disease that involves the central nervous system and associated with limbs paralysis and serious problems in sensation, limbs, visual and sphincter. This disease is a result of autoimmune mechanism in which autoantibodies target the self-myelin antigens and cause demyelination. Because of the myelin dysfunction, MS is clinically identified with neurological disabilities. Furthermore, it can be entered into the progressive phase because of irreversible neurodegeneration and axons damage. Unfortunately, there is no effective therapeutic method for this disease and current medications have been focused on amelioration of symptoms and chronic inflammation. Although current immunotherapies ameliorate the reactivity of autoimmune anti-myelin and MS relapse rate, there is no approved method for improvement of the disease progression and repairing of the damaged myelin. Therefore, finding an appropriate clinical treatment for improvement of neurological damages in MS patients is essential. Mesenchymal stem cells (MSCs) are multipotent cells with high proliferative and self-renewal capacities, as well as immunomodulatory and neuroregenerative effects. Bone marrow and adipose tissues derived MSCs have been considered for the treatment of different diseases because not only they can be easily isolated from these tissues, but also a patient can be served as a donor for himself without the risk of rejection. More importantly, autologous MSCs carry a safer pattern without the risk of malignant transformation. Here, we will discuss the effectiveness of MSCs therapy for MS patients by reviewing of clinical trials.